2022
DOI: 10.3390/cells11030409
|View full text |Cite
|
Sign up to set email alerts
|

S-Adenosylmethionine: From the Discovery of Its Inhibition of Tumorigenesis to Its Use as a Therapeutic Agent

Abstract: Alterations of methionine cycle in steatohepatitis, cirrhosis, and hepatocellular carcinoma induce MAT1A decrease and MAT2A increase expressions with the consequent decrease of S-adenosyl-L-methionine (SAM). This causes non-alcoholic fatty liver disease (NAFLD). SAM administration antagonizes pathological conditions, including galactosamine, acetaminophen, and ethanol intoxications, characterized by decreased intracellular SAM. Positive therapeutic effects of SAM/vitamin E or SAM/ursodeoxycholic acid in animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 174 publications
(263 reference statements)
0
22
0
1
Order By: Relevance
“…Beyond targeting protein functions, more and more evidence has demonstrated that natural agents exert antitumor activities by altering miRNA expression, providing a new approach to develop innovative and more efficient anticancer strategies based on synergistic combinatorial therapies [ 20 ]. In this context, S-adenosyl- l -methionine (AdoMet), a multitargeted and safe FDA-approved natural compound and the universal biological methyl donor in transmethylation reactions, has emerged, over the past two decades, as a promising anticancer therapeutic agent [ 21 , 22 ]. Recently, the antiproliferative properties of AdoMet and its implication in multiple cellular processes including proliferation, differentiation, cell cycle regulation, and apoptosis in various tumor cells have been thoroughly examined in the literature [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], and several findings have highlighted the therapeutical potential of AdoMet as an effective adjuvant to chemotherapeutic agents to be used in combined therapy to overcome drug resistance [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond targeting protein functions, more and more evidence has demonstrated that natural agents exert antitumor activities by altering miRNA expression, providing a new approach to develop innovative and more efficient anticancer strategies based on synergistic combinatorial therapies [ 20 ]. In this context, S-adenosyl- l -methionine (AdoMet), a multitargeted and safe FDA-approved natural compound and the universal biological methyl donor in transmethylation reactions, has emerged, over the past two decades, as a promising anticancer therapeutic agent [ 21 , 22 ]. Recently, the antiproliferative properties of AdoMet and its implication in multiple cellular processes including proliferation, differentiation, cell cycle regulation, and apoptosis in various tumor cells have been thoroughly examined in the literature [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], and several findings have highlighted the therapeutical potential of AdoMet as an effective adjuvant to chemotherapeutic agents to be used in combined therapy to overcome drug resistance [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, S-adenosyl- l -methionine (AdoMet), a multitargeted and safe FDA-approved natural compound and the universal biological methyl donor in transmethylation reactions, has emerged, over the past two decades, as a promising anticancer therapeutic agent [ 21 , 22 ]. Recently, the antiproliferative properties of AdoMet and its implication in multiple cellular processes including proliferation, differentiation, cell cycle regulation, and apoptosis in various tumor cells have been thoroughly examined in the literature [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], and several findings have highlighted the therapeutical potential of AdoMet as an effective adjuvant to chemotherapeutic agents to be used in combined therapy to overcome drug resistance [ 28 , 29 , 30 , 31 ]. More and more evidence has also shown that the epigenetic modulation of miRNAs involved in oncogenic functions represents one of the main mechanisms underlying the anticancer activity of AdoMet.…”
Section: Introductionmentioning
confidence: 99%
“…The transition from MAT1A to MAT2A/B results in a decrease in the level of hepatic SAM . A switch in the gene expression from MAT1A to MAT2A in human-derived hepatocellular carcinoma cells and hepatoma tissues can affect cell growth and is related to the malignant transformation of hepatocellular carcinoma. In addition, MAT2A replaces MAT1A as the predominant isoform in the process of tumorigenesis, which is particularly important at the pathological level because the expression of MAT2A is related to the low level of SAM and rapid cell growth . SAM is a major intracellular methylation donor, and epigenetic changes, including DNA methylation, are considered to be major features of HCC. , Data show that the recurrence rate of liver cancer patients with overexpression of MAT2A increases within 1 year after hepatectomy, while the upregulation of MAT1A is negatively associated with tumors.…”
Section: Mat2a Biology and Its Relation To Cancermentioning
confidence: 99%
“…SAM is an important metabolite that participates in multiple critical reactions for infant development, including phosphatidylcholine, polyamine, and carnitine biosynthesis, or DNA and protein methylation [ 8 ]. SAM is also available in several countries as an over-the-counter dietary supplement, which is supported by numerous clinical trials indicating its efficacy in the treatment of a wide range of conditions, including depression [ 9 , 10 ], hepatic disorders [ 11 , 12 ], and osteoarthritis [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%